Leprosy in 3-year-old twin children in Mato Grosso, Brazil - José Cabral Lopes; Pietra Andrade de Osti; Leticia Rossetto da Silva Cavalcante; Ciro Martins Gomes; Amílcar Sabino Damazo (Hansenologia Internationalis, 2022)
Introduction: Mycobacterium leprae is a microorganism that cause leprosy; it has a long, silent, and consumptive evolution. Case Report: twin children with three years old were contactants of a leprosy patient in the family. The two patients have well-defined and irregular skin lesions. Also, they have the BCG-vaccine scar. They were confirmed positive to Mycobacterium by histopathological analysis. Discussion: Especially under five years old, diagnoses are rare and difficult because they simulate other diseases, especially rheumatology. These diagnoses are epidemiological alarms for endemic areas. It shows the importance of symptoms in children and the screening in patients' contact already identified.